Preparation method of cathode catalyst and anode plate for neutral zinc-air battery
The M-N-C catalyst prepared by plasma discharge ball milling and heat treatment is used as a cathode catalyst for neutral zinc air batteries, which solves the problems of slow oxygen reaction kinetics, large overpotentials and low energy efficiency, and achieves higher energy efficiency and cycling performance.
Patent Information
- Application Number
- CN202411583021.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Neutral zinc air batteries have slow positive oxygen reaction kinetics, large overpotentials and low energy efficiency.
The M-N-C catalyst was prepared by a two-step method of plasma discharge ball milling and heat treatment, and a carbon material containing transition metals and nitrogen elements was incorporated into the cathode catalyst for neutral zinc air batteries.
It significantly reduces the overpotential of the battery reaction, improves energy efficiency, improves the kinetics of the oxygen reaction, and the preparation process is simple, green, pollution-free, and is easy to produce in large quantities.
Smart Images

Figure CN119419289A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zinc-air batteries, and in particular relates to a cathode catalyst material suitable for neutral zinc-air batteries and a preparation method thereof. Background Art
[0002] Zinc-air batteries are considered to be the best among high-energy-density battery solutions due to their advantages such as high specific energy, high safety, and low cost. Among them, alkaline zinc-air primary batteries have long been maturely used in high-performance hearing aids and other precision electronic devices that require continuous voltage regulation. Since it is difficult for the zinc negative electrode to achieve a stable dissolution-deposition cycle during the battery charging and discharging process in an alkaline electrolyte environment, the solution using a neutral zinc salt electrolyte has become the preferred choice in many zinc-air secondary battery studies. Among them, zinc-air secondary batteries using neutral Zn(OAc)2 electrolytes have good calendar life and cycle stability, but their slow reaction kinetics in the ORR / OER process lead to low energy efficiency. Therefore, it is crucial to develop efficient catalysts that promote oxygen electrochemistry for the battery positive electrode. MNC catalysts have been proven to be materials with excellent ORR catalytic activity. Traditional MNC catalysts are mostly prepared by wet chemical methods, which are cumbersome and have low yields. This patent prepares MNC catalysts by a two-step method of plasma discharge ball milling followed by heat treatment. The preparation is simple and does not involve chemical solvents. The process is green and pollution-free and easy to produce in large quantities and continuously, and has high practical significance and application value. Summary of the invention
[0003] In order to solve the problems of slow oxygen reaction kinetics, large overpotential and low energy efficiency in the positive electrode of neutral zinc-air batteries, the present invention aims to provide a new process for preparing catalyst materials for the positive electrode of neutral zinc-air batteries. The process is simple and does not use chemical solvents; it is green and pollution-free, has a high material input-output ratio and is easy to prepare in large quantities continuously. After the catalyst obtained by this scheme is applied to the positive electrode of a neutral zinc-air battery, the overpotential of the battery reaction is significantly reduced and the energy efficiency is significantly improved.
[0004] The technical principle adopted by the present invention is as follows: a MNC cathode catalyst for a neutral zinc-air battery, wherein the cathode catalyst is a carbon material doped with a transition metal M and a nitrogen element. In a high-purity nitrogen atmosphere, a metal ball composed of M is used to perform plasma discharge ball milling on carbon powder. In a high kinetic energy state, the metal ball is used as a plasma anode target to sputter out an M element plasma atmosphere, which is deposited on the surface of the carbon material together with partially dissociated nitrogen atoms. Continuous high-energy ball milling allows the surface of the carbon material to be uniformly deposited with equal probability during the entire discharge process. Finally, the catalyst precursor obtained is subjected to high-temperature treatment to achieve component solidification, thereby increasing the service life of the catalyst.
[0005] The technical solution of the present invention is a method for preparing a cathode catalyst for a neutral zinc-air battery, the method comprising:
[0006] Step 1: Add one or more solid metal balls and carbon powder into a plasma ball mill and seal the mouth of the ball mill;
[0007] Step 2: Replace the air in the ball mill with nitrogen;
[0008] Step 3: Fix the sealed and nitrogen-filled ball milling jar on the plasma ball mill to perform plasma ball milling;
[0009] Step 4: After the ball milling is stopped, the product is allowed to stand and cool sufficiently and then taken out in an inert gas environment;
[0010] Step 5: Place the obtained product in a tube furnace and perform high temperature heat treatment under an inert gas atmosphere.
[0011] Furthermore, the specific method of step 2 is: use a vacuum pump to evacuate the tank to a low pressure state and then switch the gas line to fill it with nitrogen. After the replacement process is repeated several times, the gas valve is closed.
[0012] Furthermore, the solid metal ball is made of one or more transition metals.
[0013] Furthermore, the solid metal ball is made of Fe, Co, Ni or Cu, and the diameter of the ball is 3 to 15 mm. Balls of two or more sizes need to be added during grinding.
[0014] Furthermore, the carbon powder is one or more of carbon black, carbon nanotubes, acetylene black, graphite or graphene, and the powder particle size does not exceed 100 μm.
[0015] Furthermore, the total volume of the transition metal M grinding balls and the carbon powder does not exceed one third of the volume of the ball mill.
[0016] Furthermore, during the grinding process, the motor vibration speed is 300 to 800 revolutions per minute, and the single rotation time is 20 to 30 minutes and then the machine is stopped for 5 to 10 minutes. The machine is run and stopped in a cycle for 10 to 30 times in sequence and then fully cooled.
[0017] Furthermore, the inert gas atmosphere in the high temperature treatment is one of high purity nitrogen or high purity argon, the heat treatment temperature of the tubular furnace in the high temperature treatment is 600-1500° C., the insulation time is 1-12 hours, and the heating rate is 4-8° C. / min.
[0018] Furthermore, a method for manufacturing a positive electrode plate using the catalyst is provided, the method comprising:
[0019] The cathode catalyst, binder and solvent are mixed and stirred to obtain slurry, and the slurry is evenly coated on the hydrophobic carbon paper, and the positive electrode sheet is obtained after standing and drying.
[0020] Furthermore, the cathode catalyst, binder and solvent are mixed in a ratio of 9:1:20, and the slurry is evenly coated on the hydrophobic carbon paper with a total dry matter content of 15 to 30 mg / cm 2 .
[0021] Furthermore, the binder is polytetrafluoroethylene or polyvinylidene fluoride, and the dispersant is an organic alcohol.
[0022] Compared with other existing technologies, the beneficial effects of the present invention are as follows:
[0023] The method for preparing the catalyst of the present invention is simple, and the target catalyst can be obtained by ball milling and heat treatment; no chemical solvent is involved in the preparation process, and it has green economy; the material input-output ratio is very high, and it has the potential for large-scale continuous synthesis; by replacing the grinding ball, the controllable doping of multiple transition metal elements can be achieved, and it has high universality. The synthesized catalyst in this scheme is applied to the positive electrode of the neutral zinc-air battery, which can effectively improve the oxygen reaction kinetics and reduce the cathode overpotential. The finished battery shows excellent rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the X-ray powder diffraction pattern of the Fe-NC powder prepared in Example 1 of the present invention.
[0025] Figure 2 This is a low-magnification scanning electron microscope image of the Fe-NC powder prepared in Example 1 of the present invention.
[0026] Figure 3 This is a high-magnification scanning electron microscope image of the Fe-NC powder prepared in Example 1 of the present invention.
[0027] Figure 4 This is the full XPS spectrum of the Fe-NC powder prepared in Example 1 of the present invention.
[0028] Figure 5 This is the N1s high-resolution XPS spectrum of the Fe-NC powder prepared in Example 1 of the present invention.
[0029] Figure 6 This is the Fe 2p high-resolution XPS spectrum of the Fe-NC powder prepared in Example 1 of the present invention.
[0030] Figure 7 When the Fe-NC and pure VXC-72 carbon black prepared in Example 2 of the present invention are used as the positive electrode catalyst layer of the zinc-air battery, the current density is 0.1 mA cm -2 , with a surface capacity of 1 mAh cm -2 Below is a comparison of the charge and discharge curves of neutral zinc-air batteries.
[0031] Figure 8 When the Fe-NC and pure VXC-72 carbon black prepared in Example 2 of the present invention are used as the positive electrode catalyst layer of the zinc-air battery, the current density is 1 mA cm -2 , with a surface capacity of 1 mAh cm -2 Below is a comparison of the charge and discharge curves of neutral zinc-air batteries.
[0032] Fig. 9 When the Fe-NC and pure VXC-72 carbon black prepared in Example 2 of the present invention are used as the positive electrode catalyst layer of the zinc-air battery, the current density is 4 mA cm -2 , with a surface capacity of 1 mAh cm -2 Below is a comparison of polarization curves of neutral zinc-air batteries.
[0033] Fig.10 When the Fe-NC and pure VXC-72 carbon black prepared in Example 2 of the present invention are used as the positive electrode catalyst layer of the zinc-air battery, the current density is 0.1 mA cm -2 , comparison of constant current discharge curves of neutral zinc-air batteries. DETAILED DESCRIPTION
[0034] Example 1 Preparation of cathode catalyst - Fe-NC material
[0035] The Vulcan XC-72R carbon black powder used in this embodiment has a particle size of 30 nm.
[0036] The iron ball used in this embodiment is a solid pure iron ball with a diameter of 6 mm.
[0037] The nitrogen used in this embodiment is high-purity nitrogen with a purity higher than 99.999%.
[0038] The ball mill used in this embodiment is a PBMS plasma ball mill produced by Nanrui New Materials.
[0039] The model of the tube furnace used in this embodiment is Hefei Kejing OTF-1200X-S.
[0040] (I) The preparation method is as follows:
[0041] 1. First, weigh 200g of solid iron balls and 2g of carbon black powder, place them in a ball mill, tighten the screws, and seal the ball mill.
[0042] 2. Use a vacuum pump to extract the air in the ball mill to put it in a low-pressure state, and then fill it with 0.5MPa nitrogen. Repeat this exhaust and inflation process 5 times.
[0043] 3. Fix the ball mill on the ball mill, connect the wires on the ball mill, turn on the power, set the motor vibration speed of the ball mill to 500RPM, the AC frequency to 10kHz, the single rotation time to 30 minutes, stop for 10 minutes, and run and stop alternately for 20 times in sequence until the reaction is completed. After the reaction is completed, it needs to be left to stand for 12 hours to completely cool down before opening the ball mill to prevent the high-temperature and highly active carbon powder from coming into contact with the air and burning violently.
[0044] 4. The obtained powder is loaded into a porcelain boat and placed in a tubular furnace for high-temperature heat treatment under a nitrogen atmosphere. The treatment temperature is 800°C, the insulation time is 2 hours, and the heating rate is 5°C / min. After the insulation time, the temperature is naturally lowered. After reaching room temperature, the sample is removed to obtain the required iron-nitrogen-carbon material.
[0045] (II) Material Characterization
[0046] Figure 1 is the X-ray powder diffraction pattern of Fe-NC powder. Figure 1 It can be seen that in addition to the carbon peak, an iron-containing peak appears near 44°, indicating that there are a large number of iron atom agglomerates in the carbon powder.
[0047] Figure 2 and Figure 3 The scanning electron microscope image of Fe-NC. Figure 2 and Figure 3 It can be seen that the carbon powder after ball milling is no longer granular, but will agglomerate into blocks with iron particles attached to them.
[0048] Example 2 Application of cathode catalyst in neutral zinc-air battery
[0049] The electrolyte used in this embodiment is 1 mol / L zinc acetate solution.
[0050] The zinc sheet used in this embodiment has a thickness of 0.05 mm and a diameter of 12 mm.
[0051] The tin foil used in this embodiment has a thickness of 0.03 mm and a diameter of 16 mm.
[0052] The membrane used in this example is Whatman GF / A.
[0053] The battery mold used in this embodiment is a Swagelok type battery.
[0054] (I) Preparation of air positive electrode
[0055] The Fe-NC cathode catalyst, polytetrafluoroethylene and isopropanol were mixed in a mass ratio of 9:1:10, stirred evenly to obtain a slurry, and the slurry was evenly coated on a hydrophobic carbon paper, allowed to stand and dry, and then cut into a diameter of 12 mm using a tablet press to obtain a positive electrode sheet.
[0056] (II) Zinc-air battery assembly
[0057] Assembly method: The positive electrode sheet prepared in (a) is used as the positive electrode of the zinc-air battery, and the zinc sheet is used as the negative electrode of the zinc-air battery. First, place the tin foil on the base, then put the zinc sheet, then put two GF / A diaphragms with a diameter of 12 mm, then drop 200 μL of 1 mol / L Zn(OAC)2 electrolyte, and then put the positive electrode sheet, with the side coated with the catalyst facing the contact diaphragm, and finally align and tighten the shell so that the current collector fully contacts the positive carbon paper.
[0058] Comparative Example - Zinc-air battery with pure Vulcan XC-72R carbon black positive electrode: When preparing the positive electrode, pure carbon black, polytetrafluoroethylene and isopropyl alcohol are mixed in a mass ratio of 9:1:10, stirred evenly to obtain a slurry, and the slurry is evenly coated on a hydrophobic carbon paper, left to dry, and then cut to a diameter of 12 mm using a tablet press to obtain a positive electrode sheet. The sheet is used as the positive electrode of the zinc-air battery, and the assembly method is the same as (II).
[0059] (III) Battery performance test
[0060] The neutral zinc-air battery was subjected to charge and discharge tests at different currents, constant current charge and discharge tests, and constant current long discharge performance tests. The battery tests were all carried out on the Xinwei battery testing system.
[0061] 1. At a current density of 0.1 mA cm -2 , the surface capacity is 1 mA·h cm -2 The neutral zinc-air battery was tested under constant current charge and discharge cycle conditions. Figure 4 As shown in the figure, the voltage polarization of the zinc-air battery with pure VXC-72 carbon black as the positive electrode gradually increased after stable operation for 200 hours. The zinc-air battery with Fe-NC catalyst as the positive electrode ran smoothly for 350 hours, and then failed due to the drying of the electrolyte. In the whole cycle, its voltage polarization was smaller than that of the zinc-air battery with pure VXC-72 as the positive electrode. At a current density of 1 mA cm -2 , with a surface capacity of 1 mAh cm -2 The neutral zinc-air battery was tested under constant current charge and discharge cycle conditions. Figure 5 As shown in the figure, the voltage polarization of the zinc-air battery with pure VXC-72 carbon black as the positive electrode gradually increased after stable operation for 30 hours. However, the polarization of the zinc-air battery with Fe-NC catalyst as the positive electrode increased suddenly after stable operation for 50 hours. In the same corresponding cycle, the catalyst positive electrode has a smaller polarization voltage and higher energy efficiency. At a current density of 4 mA cm -2 , with a surface capacity of 1 mAh cm -2The neutral zinc-air battery was tested for charge and discharge. Figure 6 As shown. The zinc-air battery with Fe-NC catalyst as the positive electrode has a higher discharge potential and a lower charge potential, that is, a higher energy density. These show that Fe-NC materials have good catalytic properties and can reduce the overpotential of the battery and improve the cycle performance at different current densities.
[0062] 2. At a current density of 0.1 mA cm -2 The neutral zinc-air battery was tested under constant current discharge conditions. Figure 7 The discharge potential of the zinc-air battery with pure VXC-72 carbon black as the positive electrode gradually decreased after 100 hours of discharge until it dropped to the cut-off voltage of 0.2V, while the zinc-air battery with Fe-NC catalyst as the positive electrode ran smoothly for more than 200 hours, with the discharge potential almost maintained above 1V, and the utilization rate of the zinc negative electrode exceeded 72%.
[0063] In summary, the Fe-NC catalyst material has many advantages: simple preparation method, high input-output ratio, green and pollution-free, low cost, and is expected to be prepared in large quantities. At the same time, when it is used as the positive electrode catalyst layer of the neutral zinc-air battery, it can effectively reduce the overpotential of the battery and improve the cycle performance of the battery. It can also be used as a positive electrode catalyst for a primary zinc-air battery to improve the stability of the discharge battery and increase the utilization rate of the zinc negative electrode.
Claims
1. A method for preparing a cathode catalyst for a neutral zinc-air battery, the method comprising: Step 1: Add one or more solid metal balls and carbon powder into a plasma ball mill and seal the mouth of the ball mill; Step 2: Replace the air in the ball mill with nitrogen; Step 3: Fix the sealed and nitrogen-filled ball milling jar on the plasma ball mill to perform plasma ball milling; Step 4: After the ball milling is stopped, the product is allowed to stand and cool sufficiently and then taken out in an inert gas environment; Step 5: Place the obtained product in a tube furnace and perform high temperature heat treatment under an inert gas atmosphere.
2. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: The specific method of step 2 is: use a vacuum pump to evacuate the tank to a low pressure state and then switch the gas line to fill it with nitrogen. After the replacement process is repeated several times, close the gas valve.
3. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: The solid metal ball is made of one or more transition metals.
4. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: The solid metal ball is made of Fe, Co, Ni or Cu, with a diameter of 3 to 15 mm. When grinding, it is necessary to add balls of two or more sizes.
5. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: The carbon powder is one or more of carbon black, carbon nanotubes, acetylene black, graphite or graphene, and the powder particle size does not exceed 100 μm.
6. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: The total volume of transition metal M grinding balls and carbon powder should not exceed one third of the volume of the ball mill.
7. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: During the grinding process, the motor vibration speed is 300-800 revolutions per minute. After a single rotation time of 20-30 minutes, the machine will be shut down for 5-10 minutes. The machine will be run and shut down 10-30 times in sequence and then fully cooled.
8. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: The inert gas atmosphere in the high temperature treatment is one of high purity nitrogen or high purity argon. The heat treatment temperature of the tubular furnace in the high temperature treatment is 600-1500°C, the insulation time is 1-12 hours, and the heating rate is 4-8°C / min.
9. The method for preparing a cathode catalyst for a neutral zinc-air battery according to claim 1, characterized in that: A method for manufacturing a positive electrode plate using the catalyst, the method comprising: The cathode catalyst, binder and solvent are mixed and stirred to obtain slurry, and the slurry is evenly coated on the hydrophobic carbon paper, and the positive electrode sheet is obtained after standing and drying.
10. A method for preparing a positive electrode sheet from a cathode catalyst prepared by the method of claim 1, characterized in that: The cathode catalyst, binder and solvent are mixed in a ratio of 9:1:
20. The slurry is evenly coated on the hydrophobic carbon paper. The total dry matter per unit area is 15-30 mg / cm 2 .
Citation Information
Patent Citations
Preparation method for WC-Co cemented carbide
CN101285134A
Preparing method of alumina-carbon base composite material for negative electrode of lithium ion battery
CN102420318A
Controllable preparation method and application of nitrogen-doped carbon-coated nickel-iron-cobalt-based quaternary medium-entropy alloy nanospheres
CN117718484A
N and P co-doped carbon-based composite material, preparation method thereof and application of N and P co-doped carbon-based composite material in lead-carbon battery
CN118218587A
Synthesis method of carbon NANO wire rod
KR1020090110664A
Cited By
Asymmetric monatomic electrocatalyst, preparation method thereof and application of asymmetric monatomic electrocatalyst in zinc-air battery
CN122291546A